An Assessment of Financial Literacy Among College Students in Nepal - Acharya, Udaya Raj; Rajkarnikar, Rashmee (Janabhawana Research Journal, 2025)
This study aimed to examine in the financial literacy among Nepalese college students with respect to socio-economic characteristics, financial education experience and financial transaction experience and to examine the factors affecting the financial literacy of the students. For the construction financial literacy, understanding of income, saving and investment, expenditure and debt and financial management were used. Primary data were taken from various private and public college from Kathmandu Valley from Kathmandu valley using questionnaire. 385 responses were taken for the study. T-test and F-test were used to analyze the significant differences of the financial literacy among the male and female. Hierarchical regression was used to analyze the factors of financial literacy. The study found that the students had great understanding on saving and investment and least understanding on financial management. The mean score of males in financial literacy is found to be 10.44 out of 20 while that of females is found to be 10.25 and 10.3 of total. However, no significant differences were found among the gender for financial literacy. The regression coefficient of education level of the students, financial education received at university and mobile banking services were 1.85, 0.922 and 0.64 which were statistically significant and had positive impact on financial literacy.